RGAP molecular marker for resistance against yellow mosaic disease in ridge gourd [Luffa acutangula (L.) Roxb.] - Manpreet Kaur; Varalakshmi B; Kumar M; Lakshmana Reddy D C; Mahesha B; Pitchhaimuthu M (Journal of Horticultural Sciences, 2021)
Yellow mosaic disease caused by Tomato leaf curl New Delhi virus (ToLCNDV) causes 100 percent losses in ridge gourd under epidemic conditions, particularly in the tropics and sub-tropics of India. Plant breeding approaches led by the marker-assisted selection have gained increased momentum in virus resistance breeding to hasten the development of resistant varieties. In the present study, an effort has been made to identify molecular markers linked to yellow mosaic disease resistance loci in an F2 population derived from a cross between susceptible ‘Arka Prasan’ and resistant ‘IIHR-Sel-1’ of ridge gourd. All the molecular markers were amplified in parents, and one polymorphic marker clearly distinguished the contrasting parents. The primers LaRGAP 63 produced a polymorphic DNA fragment that co-segregated with yellow mosaic disease reaction phenotypically in the F2 population. The identified marker will be helpful to the breeders for introgression of resistance loci into the elite background.